2017
DOI: 10.1111/imj.13349
|View full text |Cite|
|
Sign up to set email alerts
|

Doctors’ use of mobile devices in the clinical setting: a mixed methods study

Abstract: Doctors use mobile devices to enhance efficiency in the workplace. In the current environment, doctors are making their own decisions based on balancing the risks and benefits of using mobile devices in the clinical setting. There is a need for guidelines around acceptable and ethical use that is patient-centred and that respects patient privacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 36 publications
5
58
0
2
Order By: Relevance
“…The range of student opinions about appropriate use of mobile devices in clinical settings is in line with Rogers' () theory of diffusion of innovations, which highlights the irregular timing of individuals' adoption of new technologies. Masters et al () found that adoption of technology by students was inconsistent across a cohort, as we found with the students and clinicians(Nerminathan et al, ) and patients and carers(Alexander et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The range of student opinions about appropriate use of mobile devices in clinical settings is in line with Rogers' () theory of diffusion of innovations, which highlights the irregular timing of individuals' adoption of new technologies. Masters et al () found that adoption of technology by students was inconsistent across a cohort, as we found with the students and clinicians(Nerminathan et al, ) and patients and carers(Alexander et al, ).…”
Section: Discussionsupporting
confidence: 71%
“…It forms part of a larger study conducted in an adult and a paediatric hospital with students, physicians, patients and carers concerning use of mobile devices and attitude towards others' mobile device use. A paper published in this journal provided an overview of the entire study, with a focus on the comparisons between the participant groups (Scott, Nerminathan, Alexander, Phelps, & Harrison, ), and others outlined the specific research with patients and carers (Alexander, Nerminathan, Harrison, Phelps, & Scott, ) and physicians (Nerminathan, Harrison, Phelps, Alexander, & Scott, ).…”
Section: Introductionmentioning
confidence: 99%
“…Improving and implementing hygienic practices in hospitals is an ongoing challenge. It is surprising that to date no general national or international guidelines have been developed to best manage the risk posed specifically by mobile phones despite current research demonstrating their use by most clinical staff whilst on duty [17][18][19].…”
Section: Mobile Phones and Smartphones In Health Care Settingsmentioning
confidence: 99%
“…Many studies have revealed the effectiveness, efficiency, and superiority of m-learning. These include studies on its use in medicine (Chase et al, 2018;Lin & Lin, 2016;Nerminathan, Harrison, Phelps, Scott, & Alexander, 2017); in language learning (Alkhezzi & Al-Dousari, 2016;Chinnery, 2006;Klímová, 2018); in special education (Judge, Floyd, & Jeffs, 2015;Karanfiller, Yurtkan, Rüştüoğlu, & Göksu, 2018); and in the learning of motor skills (Hung, Shwu-Ching Young, & Lin, 2018); as well as research on the different age groups in different areas and the effects on academic achievement, attitude, motivation, and interaction. These studies have discussed m-learning in different research patterns through variables.…”
Section: Research Trends In Mobile Learningmentioning
confidence: 99%